Conhecimento de mulheres profissionais do sexo sobre HIV/Aids e sua influência nas práticas sexuais - Patrício, Anna Cláudia Freire de Araújo (2015)
ABSTRACT Introduction: the labour exercise of women sex workers favors the contagion by HIV and requires knowledge to the adherence to safe sexual practices. Objective: to analyze the knowledge of female sex workers on HIVAids, considering socio-demographic variables and the relationship of this knowledge with sexual practices. Methodology: exploratory and quantitative study, conducted from May to September 2014, with 90 women sex workers Association of Prostitutes of Paraíba, through a questionnaire with sociodemographic information and three dimensions (D3-forms of contagion and prevention, physiological and behavioral attributes of aids; D4-HIV causes symptoms in humans and D5-aids treatment) of a total of six that make up the test of scientific knowledge to HIVAids, adapted with adding a dimension about sexual practices (D7). The data were processed by the program SPSS version 19, using descriptive statistics, with scores of hits (Friedman test), absolute and relative frequency of hits and MANOVA. To correlate the D7 with the knowledge was used the Wald test and odds ratio Association. Results: professionals present an average 23.79 ± 3.84 years old; the majority (84.4%) single; 62.2% (56) with education above the high school. There is no significant difference in the averages of the percentages in the knowledge test hit by education (p=0 .476), however, there is significant difference in the average percentage of hit by dimension (p<0 .001). The D3 showed lower percentage of hits that D4 and D5. The knowledge observed on aids is underwhelming (T score). We highlight that 72.2% having sex without a condom in Exchange for a financial amount greater; they make 53.3% in menstrual period and are held in with 75.6% client showing sores on the penis or anus. It was found that despite the knowledge present statistical significant contribution in sexual practices (p>0.05), the less unsafe sexual practices, greater knowledge of HIVAids. Conclusions: the professionals have a greater knowledge about aids treatment regarding the forms of transmission and prevention, as well as adoption of unsafe sexual practices, favoring a vulnerability to infection by HIV. There was no influence of knowledge on HIVAids on sexual practices. Therefore, it is essential that the intensification of new strategies for change of behavior of these women to a sexual practice safe.